Temu Kembali Citra Busana Muslimah Berdasarkan Bentuk Menggunakan Curvature Scale Space (CSS) - Hayatun Maghfirah; Fitri Arnia; Khairul Munadi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Nowadays in Indonesia, Islamic woman's clothing has been popular and follows the latest trend. Clothing with various color, texture, and shape are available. Furthermore, the online clothing trading system is becoming more attractive, which facilitates the users the apparel images through the websites. These images can be retrieved by querying a text to the retrieval system. However, the users face difficulties in describing the clothes precisely. Thus, a retrieval method based on content, which is known as content-based image retrieval (CBIR), is developed. Here, the content is represented by color, texture, and shape. This paper aims to present and discuss an application of Curvature Scale Space (CSS) as a shape feature for Islamic woman's clothing retrieval system. The performance of retrieval results of three clothing categories is analyzed: blouse-pant, long dress, and tunic, and used different feature length. The simulations run with as many as 300 images from the three categories, 100 images from each. Performance is measured in recall and precision. The results are compared by applying another shape feature; that is the histogram of gradient (HOG). The blouse-pant group achieves the highest performance, followed by tunic and long dress categories. The different feature length affects the retrieval performance; the longer the features, the lower recall and precision values. The feature of length 4 achieves the highest performance. The CSS is applied as the feature in CBIR of Islamic clothing, results in higher performance than the HOG.